Patient Characteristics Related to Phlebitis in the East Coast of Peninsular Malaysia Hospital - Azlina Daud; Fatimah Mohamad (Jurnal Keperawatan Indonesia, 2021)
The insertion of peripheral intravenous catheters (PIVCs) is common for treatment among hospitalized patients. However, this procedure usually fails before the end of therapy because of several complications, including phlebitis. Therefore, this study aimed to determine the incidence and associated factors of phlebitis among patients with PIVC. A prospective cohort study was conducted in one of the hospitals located in East Coast Malaysia. The presence of phlebitis was assessed using the visual infusion phlebitis score checklist. The patients were followed until PIVC removal. A total of 321 data were collected among patients who received a new PIVC in the medical, gynecology, and orthopedic wards. The incidence of phlebitis was 36.1% (n= 116), and 96.6% of which were grade II. Patients aged 60 years (51.5%), men (42.2%), no known phlebitis history (47.4%), and with chronic disease record (46.8%) were determined as the highest percentage with phlebitis. This study demonstrated that age, gender, and chronic diseases were risk factors of developing phlebitis.Abstrak Karakteristik Pasien yang Berhubungan dengan Flebitis di Rumah Sakit Pantai Timur Semenanjung Malayía. Di antara pasien yang dirawat di rumah sakit, penyisipan kateter intravena perifer (PIVC) umum untuk pengobatan. Namun, prosedur ini seringkali gagal sebelum terapi selesai karena beberapa komplikasi. Salah satu komplikasi yang terjadi adalah flebitis. Oleh karena itu, penelitian ini bertujuan untuk menentukan kejadian dan faktor-faktor terkait flebitis di antara pasien dengan PIVC. Sebuah studi kohort prospektif dilakukan di salah satu rumah sakit yang berlokasi di Pantai Timur Malaysia. Kejadian flebitis dinilai menggunakan daftar periksa skor Visual Infusion Phlebitis (VIP). Para pasien ditindaklanjuti sampai pengangkatan PIVC. Terdapat 321 data yang dikumpulkan di antara pasien yang menerima PIVC baru di bangsal medis, ginekologi, dan ortopedi. Insiden flebitis ditemukan 36,1% (n= 116), 96,6% di antaranya adalah grade II. Pasien berusia 60 tahun (51,5%), pria (42,2%), pasien tidak memiliki riwayat flebitis (47,4%) dan pasien dengan catatan penyakit kronis (46,8%) tercatat sebagai persentase tertinggi dengan flebitis. Studi ini menunjukkan bahwa usia, jenis kelamin, dan pasien dengan penyakit kronis kemungkinan besar mengalami flebitis. Kata Kunci: flebitis, kateter intravena peripheral, pasien dewasa